Enhancing faecal sludge dewaterability and end-use by conditioning with sawdust and charcoal dust. Issue 3 (1st February 2018) - Semiyaga, Swaib; Okure, Mackay A. E.; Niwagaba, Charles B.; Nyenje, Philip M.; Kansiime, Frank
ABSTRACT: Faecal sludge (FS) treatment in urban slums of low-income countries of sub-Saharan Africa is poor or non-existent. FS contains over 90% water and therefore dewatering it within slums decreases transport costs, facilitates local treatment and end-use. This study was designed to enhance the dewatering efficiency of FS, using two locally available physical conditioners (sawdust and charcoal dust), each applied at dosages of 0%, 25%, 50%, 75%, 100% and 125% TS. The optimum dosage for both conditioners occurred at 50% and 75% for cake moisture content and capillary suction time, respectively. The dewatering rate improved by 14.3% and 15.8%, whereas dewatering extent (% cake solids) improved by 22.9% and 35.7%, for sawdust and charcoal dust, respectively. The dewatering in FS conditioned with sawdust and charcoal dust was mainly governed by absorption and permeation (porosity), respectively. The FS calorific value improved (from 11.4 MJ kg −1 ) by 42% and 49% with 50% TS dosage of sawdust and charcoal dust, respectively. The FS structure also became porous after dewatering which hastens the subsequent drying and/or composting processes. Due to comparable performance in dewatering, sawdust or charcoal dust, whichever is locally available, is recommended to treat FS in low-income urban slum settlements.